Kajian Strategi Daya Saing dan Inovasi Produk Kopi Nescafe dalam Dinamika Pasar Global - Revo Abdul Kholik (GLOBAL SCIENTS PUBLISHER, 2025)
This study analyzes the competitive strategies and product innovation implemented by Nescafe, one of the world's leading instant coffee brands, in facing intense market competition and evolving consumer preferences. The research examines how Nescafe leverages economies of scale, product differentiation through innovation, and effective marketing strategies to maintain and expand its market share. This analysis also highlights the critical role of continuous innovation, both in product formulation and production processes, to ensure the brand's relevance amidst evolving coffee consumption trends. Data was collected through literature reviews, industry reports, and relevant publications. The findings suggest that a combination of low-cost strategies, innovative differentiation, and adaptation to local market needs are key to Nescafe's success.